PARADIGMA SCAFFOLDING:ALTERNATIF PEMBELAJARAN SAINS SEBAGAI STIMULUS SISWA SADAR LINGKUNGANDI SDIT LUKMANUL HAKIM LANGSA - Rita Sari (BIOLINK (Jurnal Biologi Lingkungan Industri Kesehatan), 2017)
The 21st century learning science paradigm is not simply recite facts and understanding the concept but should be able to explain how to build skills to solve problems together. The purpose of this research is to describe; (1)  the granting of aid (schaffolding) by teachers and students to other students who are still in need of assistance in the teaching and learning process, and (2) to describe student behavior after learning over at the SDIT Lukmanul Hakim Langsa about environmentally conscious efforts. The research is used descriptive qualitative methode. Data collecting tool used is a form of observation. The results showed that the importance of environmentally conscious inculcation efforts early on to be done simultaneously and consistently by all stakeholders of the school. The easiest thing is to provide live examples to the students so that they are interested in learning science.